The effectiveness of training community mental health therapists in an evidence-based intervention for ASD: Findings from a hybrid effectiveness-implementation trial in outpatient and school-based mental health services. (April 2022) - Brookman-Frazee, Lauren; Chlebowski, Colby; Villodas, Miguel; Garland, Ann; McPherson, Julie; Koenig, Yael; Roesch, Scott
An Individualized Mental Health Intervention for ASD (AIM HI) was developed in collaboration with community stakeholders for delivery in mental health services in response to therapist- and caregiver-identified need to improve services for children with autism spectrum disorder (ASD). Primary findings from a cluster randomized Hybrid Type 1 effectiveness-implementation trial conducted in publicly funded mental health programs demonstrated the effectiveness of AIM HI therapist training on child and caregiver outcomes. This study examined therapist outcomes and therapist experience as a moderator of training effects. Mental health programs were randomized to immediate AIM HI training or usual care. Therapists and child/caregiver clients were recruited from participating programs. Therapists in the AIM HI training condition received consultation for 6 months while delivering AIM HI. Differences between training conditions were examined using multilevel modeling. Therapists receiving AIM HI training were observed to use more extensive active teaching strategies with caregivers, engagement strategies with children, strategies promoting continuity of care, and had more structured sessions with more extensively pursued skill building. Therapist licensure moderated some training outcomes. The current study provides support for evidence-based practice implementation in usual care mental health services. Lay abstract: Publicly funded mental health services play an important role in caring for school-age children with autism spectrum disorder (ASD); however, therapists report a lack of specialized ASD training, which families identity as a barrier in obtaining mental health services for their children. An Individualized Mental Health Intervention for ASD (AIM HI) was developed in collaboration with community stakeholders to respond to identified needs of children and community therapists. The current study examined the effects of therapist training in AIM HI on the changes in therapist practice, including therapists' use of evidence-based intervention strategies in session. Data were collected from a study conducted in community outpatient and school based mental health programs randomly assigned to receive AIM HI therapist training or observation of routine care. Therapist and child clients were enrolled from participating programs. Therapists in AIM HI training received training and consultation for 6 months while delivering the AIM HI intervention to a participating client; therapists in usual care delivered routine care. Both groups of therapists video recorded psychotherapy sessions which were scored by trained raters. Differences between training groups were examined using multilevel modeling. Therapists trained in AIM HI were observed to use more extensive active teaching strategies with caregivers, engagement strategies with children, strategies promoting continuity of care, and had more structured sessions with more effective pursuit of caregiver and children skill teaching. Therapist licensure moderated some training outcomes.